2007
DOI: 10.1002/tox.20301
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of heavy metals using Mytilus galloprovincialis in Safi coastal waters, Morocco

Abstract: Heavy metal concentrations of mercury, cadmium, lead, zinc, cooper, nickel, manganese, and chromium in Mytilus galloprovincialis were investigated to provide information on pollution of Safi coastal area, since these metals have the highest toxic potential. The concentration of Hg and Pb was determined by AFS and ICP-MS methods, respectively, whilst the remaining metals (Cd, Cr, Cu, Mn, Zn, and Ni) were quantified by AAS. High lead, cadmium, chromium, and mercury levels were registered in tissue samples collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
8
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 23 publications
6
32
8
7
Order By: Relevance
“…After the highest mean values occurred in 2008, a decreasing trend was observed. The Cr concentrations are similar to those of previous studies (Cevik et al 2008;Ergul et al 2007;Joksimovic et al 2011;Sunlu 2006;Topcuoglu et al 2004) while they are lower than those found on the Safi coast (Maanan 2007). In general, the Cr values were not uniform among the sampling sites.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…After the highest mean values occurred in 2008, a decreasing trend was observed. The Cr concentrations are similar to those of previous studies (Cevik et al 2008;Ergul et al 2007;Joksimovic et al 2011;Sunlu 2006;Topcuoglu et al 2004) while they are lower than those found on the Safi coast (Maanan 2007). In general, the Cr values were not uniform among the sampling sites.…”
Section: Resultssupporting
confidence: 75%
“…There were also statistically significant differences between Liman-Eceabat and Liman-Dardanos. While the findings in other reported studies were lower than the present study (Cardellicchio et al 2008;Ergul et al 2007;Sunlu 2006;Unlu et al 2008), others were higher (Cevik et al 2008;Maanan 2007). From the point of view of human health, for Pb the average weekly intake for adults (of 60 kg) was estimated to be 1.5 mg, so the PTWI Pb was 0.025 mg/kg body weight/week (FAO/WHO 2004) .…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…Việc nhiễm bẩn kim loại nặng trong các loài sinh vật tại cửa sông, ven biển đã phát hiện tại nhiều khu vực trên thế giới [5]. Trong đó, các loài động vật hai mảnh vỏ (ĐVHMV) được biết đến bởi khả năng hấp thụ và tích lũy kim loại nặng cao hơn gấp nhiều lần so với môi trường chúng sinh sống [5][6][7]. Nhờ có khả năng tích lũy cao chất ô nhiễm và có mối tương quan cao với hàm lượng kim loại nặng trong có trong môi trường, một số loài được sử dụng để làm sinh vật giám sát hiệu quả sự di chuyển và phát tán kim loại nặng theo các dòng dinh dưỡng và chuỗi thức ăn [5][6][7][8].…”
Section: Mở đầUunclassified